(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article analyzes the use of linguocultural elements in the poetry of Salim Ashur. The interrelation between language and culture in his works is explored, focusing on how cultural values are expressed through linguocultural markers related to national traditions, natural symbols, and historical references. The article examines how Ashur’s poetry reflects respect for language and culture, revealing national symbols, nature metaphors, and historical legacies that shape the cultural identity of the Uzbek people. The research is significant for understanding the linguistic and cultural dimensions of Salim Ashur’s works.